Assessing the Impact of Age on Foot Morphology and Feature Prioritisation using PERMANOVA and AHP Analysis - Nazarudin, Nazatul Aina Nasuha; Che Him, Norziha; Abd Latif, Noor Azliza; Yusof, Yusliandy (Enhanced Knowledge in Sciences and Technology, 2026)
Foot morphology changes with age advancement, which can impact the comfort and fit of footwear, as well as the long-term well-being of the foot, particularly in physically active women. Nevertheless, few studies have systematically examined age differences in foot morphology, prioritising the most important aspects of footwear design. The proposed research will investigate the existence of any meaningful differences in morphology between the different age groups, identify the most burdened characteristics of the foot due to ageing, and rank the features to design age-specific footwear. The UK Data Service provided secondary data consisting of 265 physically active women between the aged of 18-79 years. The participants were grouped six age groups, each spanning 10 years in age. Permutational Multivariate Analysis of Variance (PERMANOVA) was used to determine the overall morphological differences between the age groups. Then the univariate ANOVA was used to determine the key characteristics of an individual foot. The above features were further ranked by the Analytic Hierarchy Process (AHP). The results of the PERMANOVA indicate that age has a statistically significant impact on the overall foot morphology. Univariate ANOVA shows that there is a substantial difference between the foot width, the heel breadth, the height at 50% of the foot length, the circumference of the foot length at 50%, and the hallux valgus angle across age groups. The results of the AHP also suggest that the most significant item to consider in relation to age-specific footwear is foot width, taking into account the footwear’s heel-related dimensions. By combining PERMANOVA and AHP, a holistic method of analysis and prioritisation is achieved for understanding how the morphology of feet varies with age. These results provide a valuable understanding of the ergonomics design of footwear and preventive foot health measures designed for women at various stages of life.